A case report of Albright syndrome - F. Haghighati; A. Khorsand (Tehran University of Medical Sciences, 1994)
Albright syndrome is a rare condition, usually appears in the early years of life and characterized by bending or thickening of long bones. In girls, of endocrine glands disorders especially precocious puberty are the most common symptoms. Also, Brown pigments in the skin are another sing of this syndrome. Certain mucosal and skin pigments are considerable features of the disease. Etiology and pathogenesis of this disease is not clear and various histopathologic patterns are observed. In fact, this disease is substitution of bone tissue with fibrous connective tissue in which various degrees of bone resorption and repair of the lesion is recognizable.